Znalezisko serii wiórów ze stanowiska 9 w Dąbrówce, gm. Kowal - Osypiński, Piotr; Pyżewicz, Katarzyna (Folia Praehistorica Posnaniensia, 2015)
Archaeological excavations carried out by Patrimonium Foundation at site Dąbrówka 9, com. Kowal, in 2009 provided a unique assemblage of a series of blades made on so-called chocolate flint. Refitting of blades permitted reconstruction of core reduction stages. However, there the question arises of what was the origin of the find – a purpose for which the artefacts were brought to and finally deposited at the site. The blades were produced outside the site Dąbrówka 9 and they are represented either by very even regular ones – “select”, as well as debitage of the core reduction. Use-wear analysis, however, proved that each artefact had been at least sporadically used.